Pengaruh Tingkat Pengangguran Terbuka dan Indeks Pembangunan Manusia terhadap Kemiskinan di Sumatera Utara 2018-2023 - sari, Arsiska; Noubel Putra Nainggolan; Windi Octaviani; Theresia Enjel Octavia Sihombing; Feryanto Nababan; Joko suharianto (Universitas Muhammadiyah Surabaya, 2024)
This study aims to analyze the impact of the Open Unemployment Rate (TPT) and the Human Development Index (IPM) on the number of poor people in North Sumatra, Indonesia, from 2018 to 2023. Using a panel data model approach and secondary data from the Central Bureau of Statistics (BPS), this study employs quantitative methods to identify the relationship between these variables. The analysis results show that IPM has a significant negative impact on the number of poor people, while TPT has a positive but insignificant impact. Together, TPT and IPM contribute 99.77% to the number of poor people in North Sumatra. These findings encourage the government and stakeholders to design policy interventions aimed at increasing labor force participation and the human development index, such as skills training and economic empowerment programs. This study provides an understanding of the dynamics of poverty in North Sumatra and the factors that influence it, and provides policy recommendations to address these issues.